2011
DOI: 10.1063/1.3608140
|View full text |Cite
|
Sign up to set email alerts
|

Fermi level shifting of TiO2 nanostructures during dense electronic excitation

Abstract: Scanning Kelvin probe microscopy has been used to understand the modification of work function of TiO2 with swift heavy ion irradiation. The observed increase in contact potential difference (CPD) indicates a shift in Fermi level towards the valence band, which is due to the development of defects during the bombardment of high energy heavy ions. The change in CPD values on ion irradiation is attributed to electronic excitation induced defect concentration and surface roughness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 25 publications
4
40
1
Order By: Relevance
“…Similar type of SHI irradiation induced grain growth was also observed by other research groups [7,22]. The grains growth is expected due to generation of point defects and extended defects (oxygen vacancies) on the surface of TiO 2 due to electronic excitation [2,23]. With irradiation the defects concentration increases up to a dose of 5 × 10 12 ions cm −2 , beyond which it decreases with increasing fluence, due to annihilation of defects [7,24].…”
Section: Afm Studiessupporting
confidence: 67%
See 3 more Smart Citations
“…Similar type of SHI irradiation induced grain growth was also observed by other research groups [7,22]. The grains growth is expected due to generation of point defects and extended defects (oxygen vacancies) on the surface of TiO 2 due to electronic excitation [2,23]. With irradiation the defects concentration increases up to a dose of 5 × 10 12 ions cm −2 , beyond which it decreases with increasing fluence, due to annihilation of defects [7,24].…”
Section: Afm Studiessupporting
confidence: 67%
“…Titanium dioxide (TiO 2 ) is most widely used material because of its excellent optoelectronic properties [1][2][3][4][5]. Swift heavy ion (SHI) irradiation causes dense ionization and induces modification in its structural, morphological and electronic properties [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the semiconductors employed, TiO 2 is most widely used because of its suitable flat band potential, chemical state, non-toxicity, strong oxidation capacity and also its high photocatalytic activity. However the use of TiO 2 is impaired by its wide band gap (∼3.2 eV), which requires UV light for photoactivation, and its major limitation is higher recombination rate of the photogenerated charge carriers resulting in lower quantum yield [2][3][4][5][6][7][8]. In this regard our research group had previously reported the incorporation of the paramagnetic Mn 2+ ions in anatase lattice at Ti 4+ substitution site [9].…”
Section: Introductionmentioning
confidence: 99%